Hubungan Pola Makan Dengan Kejadian Hipertensi Pada Lansia di Desa Tual Wilayah Kerja Puskesmas Tual - Idham Soamole; Iswandi Fataruba; Windarti Rumaolat; Syahfitrah Umamity (Jurnal Rumpun Ilmu Kesehatan, 2024)
Background: There is a significant relationship between eating habits and the prevalence of hypertension in elderly citizens receiving care at community health centers. Objective: The purpose of this study was to determine whether the prevalence of hypertension in the community of Benteng Village RT 004/07, Benteng Health Centre Working Area, correlates with physical activity. Method: This study employed a cross-sectional methodology and was quantitative in nature. The sampling technique used was comprehenThe study employed a GPAQ questionnaire, a stethoscope, written consent, research tools, stationery, and data analysis procedures using Spearman's rank. tudy. Twenty-four respondents became the research sample. Results: According to the results of the Spearman rank statistical test, the incidence of hypertension in the Benteng Village community significantly correlates with physical activity (p value = 0.000), and the correlation is unidirectional (relationship coefficient = -0.324). The degree of hypertension among respondents decreased with increased physical activity. Suggestion: Community health centres can provide weekly fitness instructions for the elderly in an effort to reduce blood pressure in hypertensive patients through physical activity.